Pemberdayaan Petani Sebagai Kunci Keberhasilan Model Ketahanan Wilayah Berbasis Budidaya Pisang Cavendish - Novitasari, Yussie; Khusaini, Mohammad; Riniwati, Harsuko; Suwarno, Panji (Universitas Gadjah Mada, 2025)
ABSTRACTRegional resilience is a key component in supporting national resilience through stable food security. Cavendish bananas have significant potential as a leading commodity with growing domestic and international demand. However, the development of Cavendish banana cultivation in Indonesia still faces significant challenges, such as the attack of Fusarium wilt Tropical Race 4 (TR4), dependence on a single variety, and low adoption of modern agricultural technologies. This study aims to analyze the influence of farmer empowerment in Cavendish banana cultivation to strengthen regional resilience. Data collection was carried out through an in-depth literature review of various sources related to farmer empowerment and regional resilience based on Cavendish banana cultivation. SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats in farmer empowerment in Cavendish banana cultivation. The results indicate that farmer empowerment contributes to increased income, diversification of processed products, and strengthening agribusiness competitiveness. However, main challenges such as dependence on a single variety and vulnerability to diseases need to be addressed. This study suggests diversifying banana varieties, adopting modern agricultural technologies such as tissue culture, and strengthening government policies to improve farmers' capacity and biosecurity management. This approach is expected to create a sustainable agricultural system that is adaptive to environmental and market changes.